The Role of Chief Sustainability Officer on Sustainability Performance: Case Study on Automotive Companies in Asia - Juniarti Juniarti; Evelyn Shalomitha Sugiarto; Celsya Caeciliana; Alan Darmasaputra; Joel Tan (Institute of Research and Community Outreach - Petra Christian University, 2026)
Sustainability is increasingly viewed as a competitive advantage, not just a compliance requirement. However, there is still limited research on Chief Sustainability Officers (CSOs) in Asia, especially in the automotive sector, which plays a major role in emissions and sustainability issues. This research examines how having a CSO and the presence of CEO duality affect sustainability performance in Asian automotive companies. The research uses 570 observations from 2017 to 2024. The findings show that the presence of CSOs has a positive and significant effect on sustainability performance, while CEO duality has a significant positive effect. Research demonstrates that CEO duality moderates the partial positive effect of CSOs on sustainability performance. This implies that the presence of CEO duality influences CSO performance. The results of this research have several important implications for companies, particularly those in the automotive sector, that are considering the integration of CSOs into their organizational structures. This conclusion is because CSOs have been demonstrated to significantly enhance sustainability performance.